Religion and Negotiation of the Boundary between Majority and Minority in Québec: Discourses of Young Muslims in Montréal CÉGEPs - Stéphanie Tremblay; Marie-Odile Magnan; Catherine Levasseur (MDPI AG, 2018)
In Québec, tensions between youth immigrants’ identification and the perceived identity of the “majority group„ is evident in greater Montréal-area schools, where a plurality of ethno-cultural or religious affiliations often converge and where racism and Islamophobia are becoming major social issues (Benhadjoudja 2014; Baubérot 2014; Bilge 2013). This paper aims to explore the discourses of “minoritized„ Muslim youth pertaining to their perceived boundaries with respect to the majority group, considering the power relations at play. Ten qualitative interviews with Muslim youth born to immigrant parents and studying in colleges (CEGEPs) of the Montréal region will be analyzed. A typological analysis will reveal their main positions with regard to the majority group, which encompass ways of negotiating the border between the “Us„ and “Them,„ influenced by the process of secularism, arising from acceptance, contestation, or even a sort of exacerbation of racializing categorization. In conclusion, the social and political implications of these findings will be discussed.